AKUNTABILITAS KINERJA AKUNTAN PENDIDIK BERDASARKAN KOMPETENSI AKUNTAN DAN ETIKA PROFESIONAL ( Studi Empiris Pada Perguruan Tinggi Swasta di Bogor ) - Mukmin, Mas Nur; Wulansari, Hesti (Jurnal Akunida, 2017)
This research has purpose to know influence of competence accountant educator, professional ethics accountant performance of educator accountant at private university in Bogor. Population that is accountant educator. Samples amounted to 75 respondents from 9 private universities Bogor. Sampling method this research using non probability sampling. The analytical method used this research validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination (R2), F test and T test. Based the results the research, it is known that the competence of educators accountant simultaneously and partially influence the accountability of the accountant's performance of educators, professional ethics simultaneously influence but not partially influence the accountant's performance accountant accountability. Contribution amount influence of competence of educator accountant, professional ethics can use to explain accountant performance of 46.7 percent.Keywords: Competence, professional ethics, performance accountability